2017
DOI: 10.5897/ajar2016.11889
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of wheat commercialization in Ethiopia: The case of SARD-SC wheat project innovation platform sites

Abstract: In Ethiopia, wheat is becoming an essential source of income for farmers even though it is still a fundamental food crop. While the major proportion is kept for consumption, farmers sell part of their wheat produce. The main objectives of this paper are to assess the level of commercialization and its determinants of wheat producers in the four major producing regions. Quantitative primary data was collected from December 2013 to January 2014. The structured questionnaire was used to help collect quantifiable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 8 publications
0
4
2
Order By: Relevance
“…However, the result was in contrast with the finding of Meleaku et al. (2020) ; Wassihun et al., (2020) ; Addisu (2018) ; Tadele et al. (2017) ; that found as the level of formal education increased the level of wheat commercialization.…”
Section: Resultscontrasting
confidence: 71%
See 1 more Smart Citation
“…However, the result was in contrast with the finding of Meleaku et al. (2020) ; Wassihun et al., (2020) ; Addisu (2018) ; Tadele et al. (2017) ; that found as the level of formal education increased the level of wheat commercialization.…”
Section: Resultscontrasting
confidence: 71%
“…Also, the result was supported by Lighton and Emmanuel (2016) found that educated members of the households tend to shun rural agricultural life and instead opt for higher faster paying professions. However, the result was in contrast with the finding of Meleaku et al (2020); Wassihun et al, (2020); Addisu (2018); Tadele et al (2017); that found as the level of formal education increased the level of wheat commercialization.…”
Section: Determinants Of the Level Of Commercialization Of Sorghumcontrasting
confidence: 76%
“…The first is to stabilize domestic price and the second is to meet the overgrowing wheat demand of the consumer in the country. Wheat production is mostly farm to fork which means the farmers produce more of it for their consumption at home and less of it for the market (Gebreselassie et al, 2017;Mamo et al, 2016). But the main question is why those farmers produce wheat for only consumption?…”
Section: Wheat Production and Marketing Constraints In Ethiopiamentioning
confidence: 99%
“…This is because they mainly focus on consumption-oriented agricultural practices which exclude them from the market system. Thus, the transition from subsistence agriculture to commercial-oriented one is important to improve the income, consumption, and nutritional setup of the farm households (Tadele et al 2017). Recently there is a growing interest in developing countries to transform their subsistence agriculture into market-oriented one, and it is an indispensable pathway for poverty reduction and food security enhancement of the farm households (Tadele et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the transition from subsistence agriculture to commercial-oriented one is important to improve the income, consumption, and nutritional setup of the farm households (Tadele et al 2017). Recently there is a growing interest in developing countries to transform their subsistence agriculture into market-oriented one, and it is an indispensable pathway for poverty reduction and food security enhancement of the farm households (Tadele et al 2017). Ethiopia has adopted the commercialization of smallholder agriculture as a strategy for economic transformation which is indicated in the Growth and Transformation Plan II (NPC 2016).…”
Section: Introductionmentioning
confidence: 99%